Pengembangan Pakan Ikan Berprotein Tinggi Dari Keong Mas (Pomacea Canaliculata) Terhadap Ikan Nila (Oreochromis Niloticus) Dan Penerapannya Dalam Program Kerja Kuliah Kerja Nyata Di Masyarakat Desa Sungai Petai - Dira Yuga; Hafiz Tri Ananda; Hikmal Noor Hidayat; Silvi Listiani; Metri Mawaddah Ardana; Mala Anisa; Nasya Alysia Putri; Putri Aisah; Nasywa Amirah Fathinah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research focuses on developing high protein fish feed derived from golden snails with the addition of a mixture of fish pellets. The aim of this research is to produce high quality fish feed from available local resources and apply it in the Community Service Program (KKN) in village communities. Experimental methods were used to develop a feed formula with the right ratio of golden snails and fish pellets. The feed developed has a high protein content and a balanced nutritional composition. Furthermore, the KKN program was implemented in the village by involving students as facilitators in the socialization and application of high protein fish food to the community. The results show positive adoption of the feed by village communities and increased productivity of fish farming. This program provides dual benefits, namely increasing village community income through more efficient fish farming and supporting sustainable use of local resources.